On solubility of problems of clectromagnetoelasticity with memory - Mitropolsky , Yu. A.; Kurbanov , I. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
Questions are studied of the solvability of boundary value problems of electromagneticelasticity for media with memory. Theorems are proved on the existence and uniqueness of the solution of the indicated problems in the spaces C(0,T; W^1_2(Ω)) and C(0,T; L^2_(Ω)). In proving the existence theorem, we use the property of connected fields, the compactness method, monotonicity and generalized Gronwall-Bellman inequalities.